Reformulasi Pengaturan Penggolongan Program Siaran Televisi Nasional Berdasarkan Kelompok Usia Khalayak dalam Prespektif Perlindungan Anak - Hilmy, Fariz (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2019)
The protection of the law may also continue to be endorsed by The United Nations Convention on the Rights of the Child (commonly abbreviated as the CRC or UNCRC) that applies to States that have ratified it. Media regulators, especially television media and the government then try to control the contents of this media, one of which is the obligation to use the age classification code on television broadcast programs. Legislation and regulatory committees that oversee it have also been established by the government. KPI Regulation Number 01 / P / KPI / 03/2012 concerning Regulatory Procedure (P3) and KPI Regulation Number 02 / P / KPI / 03/2012 concerning Civil Procedure Program (SPS) also as alternative provisions in child protection as mandated by the Convention on the Rights of the Child (CRC) and Child Protection Law.Through this research, main problems related to the protection of children were found in the regulation of national television broadcast program classification based on the age group of audiences.Reformulation of the provisions of the age classification code on existing television broadcast programs is deemed necessary to prevent violations, especially related to child protection.